Comparison of 3 Devices for 24-Hour Ambulatory Blood Pressure Monitoring in a Nonclinical Environment Through a Randomized Trial. (23rd July 2020) - Nwankwo, Tatiana; Coleman King, Sallyann M; Ostchega, Yechiam; Zhang, Guangyu; Loustalot, Fleetwood; Gillespie, Cathleen; Chang, Tiffany E; Begley, Elin B; George, Mary G; Shimbo, Daichi; Schwartz, Joseph E; Muntner, Paul; et al.
Abstract: Background: The U.S. Preventive Services Task Force recommends the use of 24-hour ambulatory blood pressure monitoring (ABPM) as part of screening and diagnosis of hypertension. The optimal ABPM device for population-based surveys is unknown. Methods: We compared the proportion of valid blood pressure (BP) readings, mean awake and asleep BP readings, differences between awake ABPM readings and initial standardized BP readings, and sleep experience among three ABPM devices. We randomized a convenience sample of 365 adults to 1 of 3 ABPM devices: Welch Allyn Mobil-O-Graph (WA), Sun Tech Classic Oscar2 (STO) and Spacelabs 90227 (SL). Participants completed sleep quality questionnaires on the nights before and during ABPM testing. Results: The proportions of valid BP readings were not different among the 3 devices ( P > 0.45). Mean awake and asleep systolic BP were significantly higher for STO device (WA vs. STO vs. SL: 126.65, 138.09, 127.44 mm Hg; 114.34, 120.34, 113.13 mm Hg; P < 0.0001 for both). The difference between the initial average standardized mercury systolic BP readings and the ABPM mean awake systolic BP was larger for STO device (WA vs. STO. vs. SL: –5.26, –16.24, –5.36 mm Hg; P < 0.0001); diastolic BP mean differences were ~ –6 mm Hg for all 3 devices ( P = 0.6). Approximately 55% of participants reported that the devices interfered with sleep; however, there were no sleep differences across the devices ( P > 0.4 for all). Conclusion: Most of the participants met the threshold of 70% valid readings over 24 hours. Sleep disturbance was common but did not interfere with completion of measurement in most of the participants.